Estrutura de capital, governança corporativa e concentração de propriedade das empresas brasileiras - Sampaio, Thicia Stela Lima (2022)
Firm capital structure is related to firm financing and investment policies, and reflects firm debt diversity, exposing the firm situation and level of indebtedness to the market. In turn, corporate governance aims to protect shareholders, reduce agency conflicts, minimize information asymmetry between firm and market, and improve firm value. Ownership concentration is proposed as able to impact firm debt level considering that there are firm ownership characteristics that may matter for distinct effects: substitution, alignment of interests, entrenchment and expropriation. The objective of this research is to investigate the influence of the adoption of corporate governance practices and ownership concentration on the capital structure of Brazilian companies, taking into account private debt and subsidized debt. The sample is composed of 148 Brazilian companies with highest liquidity in the Brazilian market in the period 2010-2019. A panel data with 1,408 firm-year observations was structured. Model are estimated using the Generalized Least Squares for panel data and Logistic regression. Corporate governance was proxied by a Corporate Governance Index that comprises 28 practices spread in seven Corporate Governance dimensions. Ownership concentration was proxied by the proportion of firm voting shares held by the first up to the fifth largest shareholders. The results show the greater adoption of Corporate Governance practices does not positively influence firm the level of debt, contrary to expectations. More detailed investigation showed that specific Corporate Governance dimensions seem to favor firm debt, this is the case of practices related to “Inspection and Control”, and to “Executive Board”. On the other hand, ownership concentration seems to effectively matter for firm debt, being the effect different for private debt and subsidized debt. While there seems to be an inverted U shaped relation between ownership concentration and firm debt, the picture is the opposite when taking into account subsidized debt that appears to be favored by higher levels of ownership concentration.